Robotic Multisegment Triangular Resections as an Alternative to Sliding Leaflet Plasty. Issue 3 (May 2013) - Cheema, Faisal H.; Cheung, Stephen; Jiang, Jeffrey; Younus, Muhammad Jabran; Roberts, Harold G.
The sliding leaflet plasty of the posterior mitral leaflet is a complex procedure, both lengthy and technically challenging. A simple alternative is desirable, particularly for a minimally invasive approach. We report a distinct substitute to the conventional sliding leaflet plasty that included triangular resections of P2 and P3 using a robot. These multiple triangular resections enabled a successful mitral valve repair with satisfactory clinical and echocardiographic results. Recognizing the complexity of sliding leaflet plasties, we note that multisegment triangular resections seem to be an easy, expeditious, and effective alternative for the posterior leaflet that is readily performed via a robotic endoscopic approach.